2020
DOI: 10.1136/annrheumdis-2020-218338
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic, biomechanical and functional analyses define neutrophil heterogeneity in systemic lupus erythematosus

Abstract: ObjectivesLow-density granulocytes (LDGs) are a distinct subset of proinflammatory and vasculopathic neutrophils expanded in systemic lupus erythematosus (SLE). Neutrophil trafficking and immune function are intimately linked to cellular biophysical properties. This study used proteomic, biomechanical and functional analyses to further define neutrophil heterogeneity in the context of SLE.MethodsProteomic/phosphoproteomic analyses were performed in healthy control (HC) normal density neutrophils (NDNs), SLE ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 66 publications
2
51
2
3
Order By: Relevance
“…The reason for this can only be speculated on, but the active labour process itself may lead to increased granulocyte activation and degranulation in the placenta. 33 34 Whether activated LDG are associated with placental pathology in SLE pregnancy remains to be examined, but SLE LDG may be retained in microvasculature networks 35 and are associated with vascular inflammation. 36 37 Furthermore, SLE LDG spontaneously secrete proinflammatory cytokines and the neutrophil-attracting and activating chemokine CXCL8 12 and spontaneously form NETs that may lead to endothelial apoptosis and vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this can only be speculated on, but the active labour process itself may lead to increased granulocyte activation and degranulation in the placenta. 33 34 Whether activated LDG are associated with placental pathology in SLE pregnancy remains to be examined, but SLE LDG may be retained in microvasculature networks 35 and are associated with vascular inflammation. 36 37 Furthermore, SLE LDG spontaneously secrete proinflammatory cytokines and the neutrophil-attracting and activating chemokine CXCL8 12 and spontaneously form NETs that may lead to endothelial apoptosis and vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is also observed in chronic granulomatous disease LDGs, which lack functional NOX2 but can produce mtROS and NETs (122). SLE LDGs have stiffer biomechanical properties and are slower to migrate through microvascular mimetics in vitro (204). This may explain why LDGs are not found in affected tissues in SLE (284).…”
Section: Neutrophil Subsetsmentioning
confidence: 91%
“…Some success in stratifying interferon-high patients to anti-IFNα therapy (anifrolumab) is evident (201), although the largest clinical trials of anifrolumab (TULIP-1 and TULIP-2) found no significant differences in the response to antiinterferon therapy between the interferon-high and interferonlow patient groups (202,203). Expression of neutrophil genes within SLE whole blood has been attributed to the increase in the population of low density granulocytes (LDGs), discussed below (198), although proteomics analysis of SLE neutrophils and LDGs suggests that protein levels of MPO and other granule proteins is higher in SLE neutrophils (204). The expression of neutrophil granule protein genes in SLE whole blood is strongly associated with lupus nephritis (197,205), vascular inflammation and cardiovascular involvement (206).…”
Section: Gene Expression and Cell Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, NETs in patients with SLE occur predominantly in the LDGs subset, which displays morphologically and genetically immature characteristics and is involved in SLE development ( Mistry et al, 2019 ). The human SLE-LDGs impair phagocytic function; instead, they show pro-inflammatory properties and injure the endothelium, indicating the involvement of cardiovascular disease development in SLE ( Denny et al, 2010 ; Rahman et al, 2019 ; Bashant et al, 2021 ). Furthermore, the human LDGs comprise two subpopulations of CD10-negative immature and CD10-positive intermediate mature types based on transcriptomic and epigenetic analyses.…”
Section: Introductionmentioning
confidence: 99%